Impact of the covid-19 pandemic on the use of ICT tools in science and technology education - Álvaro Antón-Sancho; Pablo Fernández-Arias; Diego Vergara-Rodríguez (OmniaScience, 2023)
This article analyzes the self-concept about digital competence in university professors of Sciences, Health Sciences and Engineering and the impact that the COVID-19 pandemic has had on the Information and Communication Technologies (ICT) use habits of professors in these areas. For this purpose, a survey designed by the authors was completed by 340 university professors in the aforementioned areas. Based on the answers obtained from this survey, a descriptive quantitative analysis of the assessments of the self-concept of digital competence and training of the participants, of the didactic use of ICT and the frequency of their use before and after the pandemic has been carried out. The results showed that the digital competence of the professors is intermediate, but their training is valued as low, especially in Sciences and Health Sciences. The assessment of ICT is very good. The pandemic has caused a generalized increase in the use of ICT, mainly in Health Sciences, which is the area in which university students were most reluctant to use them. In addition, a gender gap which did not exist before the pandemic has been generated favoring females in the use of ICT in Science and Engineering. An age-based digital gap that existed before the pandemic has also been corrected in Health Sciences.